2018
DOI: 10.1111/sjop.12464
|View full text |Cite
|
Sign up to set email alerts
|

Effects of analytical (abstract) versus experiential (concrete) induced rumination of negative self defining memories on schizotypic symptoms

Abstract: Repetitive thought may have adaptive and functional consequences, depending on, among other things, the interpretation of the content: analytical or abstract (general and decontextualized) and experiential or concrete (specific, contextual and incidental). Studies experimentally manipulating repetitive thought have shown both the constructive consequences of the experiential mode and the dysfunctional consequences of the analytical mode. The aim of the current study is to observe the effect of analytical and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 75 publications
(88 reference statements)
0
6
0
Order By: Relevance
“…(c) Negative cognitions: abstract rumination resulted in slower decision-making in high dysphoric participants (Di Schiena, Luminet, Chang, & Philippot, 2013); increased regret after writing about a prior decision (Dey, Joormann, Moulds, & Newell, 2018); and more negative generalization in dysphoric students following a learning phase and more generalization of angry faces to the self (Van Lier, Vervliet, Boddez, & Raes, 2015;Van Lier, Vervliet, Vanbrabant, Lenaert, & Raes, 2014). (d) Psychotic experiences: abstract rumination elevated experience of schizotypic symptoms in the form of self-reported anomalous perceptions of reality (e.g., feeling someone is touching you but nobody there when you look) in university students (Ricarte, Del Rey, Ros, Latorre, & Berna, 2018;Ricarte, Ros, Fernandez, Nieto, & Latorre, 2018). Abstract thinking is also found to be particularly detrimental in prospective studies concerning intrusive thoughts (Ehring, Frank, et al, 2008), and relative to healthy controls, alcohol-dependent individuals report similar levels of concrete adaptive repetitive thinking but significantly higher levels of abstract repetitive thinking (Grynberg et al, 2016).…”
Section: Abstract Processing Stylementioning
confidence: 99%
“…(c) Negative cognitions: abstract rumination resulted in slower decision-making in high dysphoric participants (Di Schiena, Luminet, Chang, & Philippot, 2013); increased regret after writing about a prior decision (Dey, Joormann, Moulds, & Newell, 2018); and more negative generalization in dysphoric students following a learning phase and more generalization of angry faces to the self (Van Lier, Vervliet, Boddez, & Raes, 2015;Van Lier, Vervliet, Vanbrabant, Lenaert, & Raes, 2014). (d) Psychotic experiences: abstract rumination elevated experience of schizotypic symptoms in the form of self-reported anomalous perceptions of reality (e.g., feeling someone is touching you but nobody there when you look) in university students (Ricarte, Del Rey, Ros, Latorre, & Berna, 2018;Ricarte, Ros, Fernandez, Nieto, & Latorre, 2018). Abstract thinking is also found to be particularly detrimental in prospective studies concerning intrusive thoughts (Ehring, Frank, et al, 2008), and relative to healthy controls, alcohol-dependent individuals report similar levels of concrete adaptive repetitive thinking but significantly higher levels of abstract repetitive thinking (Grynberg et al, 2016).…”
Section: Abstract Processing Stylementioning
confidence: 99%
“…One of the specific types of unconstructive repetitive thinking most frequently investigated in mood and anxiety disorders is rumination. Even though various models of rumination have been conceptualized (Koster et al 2011;Krys et al 2020;Miller et al 2020;Ricarte et al 2018;Watkins and Roberts 2020), as the most influential notion, response styles theory defines rumination as patterns of passively and pervasively thinking about one's emotional symptoms as well as the causes and consequences of these symptoms (Lyubomirsky et al 2015). A tendency to ruminate about one's problems and emotions is relatively stable over time and contributes to perseveration of negative affective states (Silveira et al 2020;Whisman et al 2020), particularly self-focused rumination (Bagby et al 2004).…”
Section: Transdiagnostic Factors In Depression and Anxietymentioning
confidence: 99%
“…Ehring and Watkins, 2008). Multiple studies have investigated the processing-mode theory in various conditions other than depression (or dysphoria), such as social anxiety (Van Lier et al, 2015;Vassilopoulos and Watkins, 2009;Wong and Moulds, 2012), schizophrenia (Ricarte et al, 2018a;Ricarte et al, 2018b), and alcohol dependence (Grynberg et al, 2016; for an overview of different conditions see also Watkins and Roberts, 2020), as well as in the context of symptoms such as intrusive memories (Santa Maria et al, 2012;Schaich et al, 2013;Stavropoulos and Berle, 2020). Most of these studies have reported no differential effects of abstract and concrete rumination on affect (e.g.…”
Section: Introductionmentioning
confidence: 99%